Altered ECM deposition by diabetic foot ulcer‐derived fibroblasts implicates fibronectin in chronic wound repair. Issue 4 (8th June 2016) - Maione, Anna G.; Smith, Avi; Kashpur, Olga; Yanez, Vanessa; Knight, Elana; Mooney, David J.; Veves, Aristidis; Tomic‐Canic, Marjana; Garlick, Jonathan A.
Abstract: Current chronic wound treatments often fail to promote healing of diabetic foot ulcers (DFU), leading to amputation and increased patient morbidity. A critical mediator of proper wound healing is the production, assembly, and remodeling of the extracellular matrix (ECM) by fibroblasts. However, little is known about how these processes are altered in fibroblasts within the DFU microenvironment. Thus, we investigated the capacity of multiple, primary DFU‐derived fibroblast strains to express, produce, and assemble ECM proteins compared to diabetic patient‐derived fibroblasts and healthy donor‐derived fibroblasts. Gene expression microarray analysis showed differential expression of ECM and ECM‐regulatory genes by DFU‐derived fibroblasts which translated to functional differences in a 3D in vitro ECM tissue model. DFU‐derived fibroblasts produced thin, fibronectin‐rich matrices, and responded abnormally when challenged with transforming growth factor‐beta, a key regulator of matrix production during healing. These results provide novel evidence that DFU‐derived fibroblasts contribute to the defective matrices of DFUs and chronic wound pathogenesis.